Effect of lipid bilayer composition on membrane protein association - Pawar, Aiswarya B.; Prasanna, Xavier; Sengupta, Durba (Advances in Planar Lipid Bilayers and Liposomes, 2015)
Diverse cellular functions are supported by membrane protein assemblies associated with the cell membrane. Although considered to be protein-mediated, membrane components are now being recognized as critical in modulating and sometime dictating function. This chapter discusses the effect of the lipid bilayer, in particular its composition on membrane protein organization. Computational methods have been successful in quantifying transmembrane protein association and general features of dimerization profiles are explored. Understanding the molecular basis of the interactions has lead to the recognition of the lipophobic effects. These nonspecific effects include those that arise from membrane perturbations and lipid chain packing and have been shown to modulate the energetics as well as the structural characteristics of membrane protein dimerization. In addition, specific interactions arising from direct protein–lipid interactions and protein–cholesterol interactions have been suggested to influence membrane protein association. We summarize here a few examples highlighting the role of the lipid bilayer on membrane protein organization.

Estimating the lipophobic contributions in model membranes - Dubey, Vikas; Prasanna, Xavier; Sengupta, Durba (Journal of Physical Chemistry B, 2017)
The insertion and association of membrane proteins is critical in several cellular processes. These processes were thought to be protein-driven, but increasing evidence points toward an important role of the lipid bilayer. The lipid-mediated contribution has been shown to be important in the association of membrane peptides, but the corresponding ``lipophobic'' component has not been directly estimated. Here, we calculate the free energy of insertion for transmembrane peptides and estimate the lipophobic component from the cost of cavity formation. The free-energy calculations were performed using the coarse-grain Martini force field, which has been successful in predicting membrane protein interactions. As expected, the charged moieties have the least favorable free energy of insertion and the highest cost of cavity formation. A length dependence was observed in polyalanine peptides with the lipid-mediated component increasing nonlinearly with peptide length. Membrane fluidity was tested by varying the temperature, and opposing effects were observed for short and long peptides. The dependence of the lipid-mediated effects on peptide length and temperature was not uniform and gives valuable insight into the anisotropic nature of the membrane. The results are an important step in estimating membrane effects in protein insertion and association.

Effect of membrane composition on receptor association: implications of cancer lipidomics on ErbB receptors - Pawar, Aiswarya; Sengupta, Durba (Journal of Membrane Biology, 2018)
The association of single transmembrane receptors, such as the ErbB receptors is a key event in initiating cell signaling networks. The interactions between these receptors have been well characterized for both ligand-driven and pre-formed dimers. However, the role of the membrane in modulating association is less well understood and assumes greater importance in light of altered membrane composition in diseased states. Here, we discuss how membrane composition has been observed to induce both structural and dynamic differences in receptor association. Computational studies, especially those using coarse-grain simulations have been successful in predicting the role of the membrane and calculating the related free energy landscapes. Membrane perturbations and differences in lipid chain order, related to the lipophobic effect, have been shown to play a large role in driving membrane protein association. Further, we review lipid compositions reported in diseased conditions and its effect on transmembrane receptor association, focusing on the ErbB growth factor receptor dimers in cancer. Understanding the role of the membrane in receptor association will provide general design principles driving receptor organization, as well as help to identify novel therapeutic strategies.

Exploring GPCR lipid interactions by molecular dynamics simulations: excitements, challenges, and the way forward - Sengupta, Durba; Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2018)
Gprotein-coupled receptors (GPCRs) are seven transmembrane receptors that mediate a large number of cellular responses and are important drug targets. One of the current challenges in GPCR biology is to analyze the molecular signatures of receptor-lipid interactions and their subsequent effects on GPCR structure, organization, and function. Molecular dynamics simulation studies have been successful in predicting molecular determinants of receptor-lipid interactions. In particular, predicted cholesterol interaction sites appear to correspond well with experimentally determined binding sites and estimated time scales of association. In spite of several success stories, the methodologies in molecular dynamics simulations are still emerging. In this Feature Article, we provide a comprehensive overview of coarse-grain and atomistic molecular dynamics simulations of GPCR-lipid interaction in the context of experimental observations. In addition, we discuss the effect of secondary and tertiary structural constraints in coarse-grain simulations in the context of functional dynamics and structural plasticity of GPCRs. We envision that this comprehensive overview will help resolve differences in computational studies and provide a way forward.

Effect of citral partitioning on structural and mechanical properties of lipid membranes - Saraf, Deepashri; Porte, Sudha; Sengupta, Durba (European Physical Journal-Special Topics, 2024)
Delineating the interactions of cellular metabolites with lipid membranes and their effects on membrane physical and mechanical properties constitutes a key step for comprehensively understanding their biological function. The plant metabolite-citral is widely used in biotechnological and cosmeceutical processes, but significant gaps remain in our understanding of how it affects cellular membranes that it interacts with. In this study, we unravel the molecular mechanisms underlying the interactions of citral with compositionally distinct model membranes using atomistic molecular dynamics simulations. Specifically, we investigate two distinct membrane compositions: the neutral phosphatidylcholine-phosphatidylethanolamine (DOPC:DOPE) bilayer, representing mammalian cell membranes and the anionic phosphatidylcholine-phosphatidylglycerol (DOPC:DOPG) bilayer, mimicking bacterial cell membranes. Our simulations reveal that citral molecules readily partition into both membranes without distinct composition-dependent effects. Monomeric citral molecules localize mainly at the interface of the acyl chain region of the lipids, and a few translocation events are sampled in the simulations. Interestingly, we observe small differences in lipid fluidity although the citral molecules significantly influence the rigidity of lipid bilayers, and a higher bending modulus was observed in DOPC:DOPE lipid bilayers compared to DOPC:DOPG bilayers. Further, citral partitioning induces an increased tendency for lipid demixing in DOPC:DOPE membranes, as evidenced by the decreased values of the Shannon entropy. Our work is an important step to elucidate the molecular processes that underlie the differential impact of cell metabolites on compositionally distinct lipid membranes.